Related Factors to Streptococcus pneumoniae Invasive Infection and Clinical Manifestations: The Potential Role of Nasopharyngeal Microbiome - Dietl, Beatriz; Henares, Desirée; Boix-Palop, Lucía; Muñoz-Almagro, Carmen; Garau, Javier; Calbo, Esther (Frontiers in Medicine, 2021)
Infections of the lower respiratory tract, such as pneumonia, are one of the leading causes of death worldwide. Streptococcus pneumoniae might colonize the upper respiratory tract and is the main aetiological agent of community-acquired pneumonia (CAP). In the last decades, several factors related to the host, the microorganism and the antibiotic therapy have been investigated to identify risk factors associated with the development of invasive pneumococcal disease (IPD). Nevertheless, these factors themselves do not explain the risk of developing disease or its severity. Recently, some studies have focused on the importance of nasopharyngeal (NP) microbiome and its relation to respiratory health. This review presents existing evidence of the potential role of NP microbiome in the development of IPD.